Novel manganese tricarbonyl complexes with benzimidazole ligands: Investigation of CO-releasing, antioxidant, antibacterial, zeta potential, theoretical, and electrochemical properties - Celebi, Mutlu Sonmez; Ayvaz, Melek col; Sakar, Dolunay; Ustun, Elvan; Erturk, Omer (ELSEVIER SCIENCE SA, 2025)
Manganese(I) carbonyl complexes bearing various bioactivities are evaluated for their CO-releasing properties. Benzimidazole type molecules which are well known for their therapeutic applications are frequently used as ligands in coordination complexes. In this study, three novel manganese(I) complexes coordinated by 2substituted benzimidazoles were synthesized bearing CO-releasing properties. The synthesized complexes were characterized by various spectroscopic methods such as IR, 1H NMR, 13C NMR, LC-MS, SEM and EDX, whereas electrochemical characterization was done by cyclic voltammetry. CO-releasing properties of the complexes were analyzed by Myoglobin Assay. The antioxidant activities of the complexes were evaluated in terms of their DPPH and SOD radical scavenging capacities as well as their chelation potentials with Fe2+ depending on CO release at two different concentrations. Antibacterial activity tests were performed in order to test the complexes for their potential for various therapeutic purposes. Antimicrobial activities were tested in vitro against six human pathogenic bacteria and two fungi. The stability of complexes was checked via zetasizer measurements such as particle size and zeta potentials of the complexes at different pH values. Additionally, molecular docking was performed against the crystal structures of DNA Gyrase of E. coli (PDB ID: 1kzn), and Human peroxiredoxin 5 (PDB ID: 1hd2).
Keywords: Benzimidazoles; Manganese complexes; CO-releasing; Antioxidant; Antibacterial; DNA GYRASE; SUPEROXIDE-DISMUTASE; BIOLOGICAL-ACTIVITY; INHIBITORS; MOLECULES; MECHANISM; DOCKING; Chemistry